What Can We Do for the Parents? How Can a Society Help Future Parents Support and Care for Their Children in the Best Possible Way? - Merkaš, Marina; Batinić, Lana (Social and Personality Development in Childhood, 2025)
Becoming a parent is one of the most life-changing experiences that has long-lasting consequences for not only the individual who has taken on this new role but also the child and, consequently, the whole society. There is no formal education for being a parent, and some people naturally have more skills and feel more confident. For some people, it could be intimidating to imagine how they will handle parenting. Before outlining how we can help parents, we must gain some understanding of the complex dynamics of parenting. First, contemporary changes in parenting are described; second, parental responsibility, parental competence, and positive parenting are defined, and we briefly describe what determines parenting and parental behaviour. Then, a list of possible ways to support parents as individuals and their living conditions is provided. Keywords: parental responsibility, parental competence, positive parenting, support, parenting programmes